2017
DOI: 10.1167/iovs.17-21712
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between High-Order Aberration and Anterior Ocular Biometry During Accommodation in Young Healthy Adults

Abstract: PurposeThis study investigated the anterior ocular anatomic origin of high-order aberration (HOA) components using optical coherence tomography and a Shack-Hartmann wavefront sensor.MethodsA customized system was built to simultaneously capture images of ocular wavefront aberrations and anterior ocular biometry. Relaxed, 2-diopter (D) and 4-D accommodative states were repeatedly measured in 30 young subjects. Custom software was used to correct optical distortions and measure biometric parameters from the imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Finally, our reported spherical aberrations (Z 0 4 ) agree with a recent study by Ke and colleagues [38]. It is noted that the spherical aberrations alternate between positive and negative sign among individuals [39,40].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, our reported spherical aberrations (Z 0 4 ) agree with a recent study by Ke and colleagues [38]. It is noted that the spherical aberrations alternate between positive and negative sign among individuals [39,40].…”
Section: Discussionsupporting
confidence: 92%
“…A recent study by Krishnan, Agaoglu, and Chung (2017) reported that fixation duration influences fixation stability. Because our task was self-paced, it is was possible that the overall duration of fixation could vary between the different conditions.…”
Section: Resultsmentioning
confidence: 99%
“…48 The results of Ke et al showed that higher-order aberrations change in gradually increased accommodation stimulus: Z 4 0 decreases during −2D stimulation, and Z 3 -1 , Z 3 1 , Z 4 0 , Z 6 0 become negative during −4D stimulation and the negative change of Z 3 1 is related to the change of anterior curvature of the lens during accommodation. 49 Visual experience is considered to play an important role in regulating the axial growth of the eye, and humans also show transient changes in axial and choroidal thickness after short-term defocus exposure. Lau et al studied the relationship between high-order aberrations and axial growth in children in Hong Kong.…”
Section: The Role Of the Lens In Visual Qualitymentioning
confidence: 99%